APPLICATION OF THE THEORY OF PROBABILITY IN BUSINESS PROCESS MANAGEMENT OF TRANSPORT ENTERPRISES - KHOBTA, Mykhailo; MALAKHOVA, Yuliia; LYTVYSHKO, Liliia; SUKMANІUK, Victoriiа (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the possibilities of applying probability theory in the management of business processes of transport enterprises, which allows to reduce the level of uncertainty in route planning, demand forecasting and inventory management, optimize costs associated with maintenance, fuel stocks and logistics processes, increase safety and quality of services through risk analysis and implementation of insurance strategies, integrate digital technologies for more accurate analysis of probabilities and making optimal decisions.The purpose of the study is to analyze the basic principles of probability theory and its application in the management of business processes of transport enterprises. To identify key methods of probabilistic analysis that allow to increase the efficiency of transport management, assess risks and optimize operational processes.The object of the study is the practical application of probability theory in the management of business processes of transport enterprises.The subject of the study is methods and approaches to probability assessment and their practical use for optimizing business processes, assessing risks and increasing the efficiency of management decisions in the transport sector.Probability theory is an important tool in many scientific and practical areas. It allows you to model random phenomena, helps manage business processes in transport enterprises, assess risks and predict possible outcomes under conditions of uncertainty. The application of probability theory allows you to optimize the management of business processes in a transport enterprise, reducing costs and improving efficiency. Further research can be aimed at a deeper study of the synergy of probability theory with intelligent information systems, which will allow you to more effectively predict risks and manage business processes in the transport sector.
Keywords: probability theory; business processes; decision making; risk management; management decisions; efficiency; statistical analysis; transport enterprises